Preparation method of PEDOT conductive powder with controllable conductivity
By using anhydrous ethanol and ferric chloride in the preparation of PEDOT conductive powder and regulating the reaction conditions, the problem of difficult conductivity is solved, and stable and efficient preparation of PEDOT conductive powder is achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411520528.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In the prior art, when preparing PEDOT conductive powder, the conductivity is difficult to accurately and stably control, especially it is difficult to prepare products with a conductivity of 10-5 to 10-3S/cm, and the process is complicated and the environmental pollution is large.
Anhydrous ethanol is used as the solvent and ferric chloride is used as the oxidant. By regulating the reaction temperature, reaction time and oxidant dosage, the preparation of PEDOT conductive powder with different conductivity is achieved.
It realizes the controllability of the conductivity of PEDOT conductive powder, stable product performance, simple process, environmentally friendly, and suitable for large-scale production.
Smart Images

Figure CN119390949A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive polymers, and more specifically, relates to a method for preparing PEDOT conductive powder with controllable conductivity. Background Art
[0002] Poly (3,4-ethylenedioxythiophene) (PEDOT) is one of the most important polythiophenes. Its conductivity spans a wide range, between conductors and semiconductors. PEDOT powders with different conductivity have different uses. PEDOT conductive powder has excellent environmental stability and has broad application prospects in photovoltaics, thermoelectrics, medicine, antistatic, electromagnetic shielding and other fields.
[0003] The main methods for synthesizing PEDOT are chemical oxidation polymerization, electrochemical polymerization, chemical vapor deposition, etc. Chemical oxidation polymerization is widely used due to its relatively simple preparation method, large production scale, and good product morphology. At present, in the method of chemical oxidation polymerization, water-based suspension precipitation polymerization is mainly used, and water-insoluble EDOT monomers are dispersed into micelles or small droplets through the addition of surfactants and high-speed stirring, and polymerized into PEDOT particles with high conductivity (conductivity of 1 to 10, or higher).
[0004] Different application scenarios often have different requirements for the conductivity of PEDOT. For example, when used in materials such as conductive cloth, its conductivity is required to be as high as possible; for antistatic, wave-absorbing and other materials, its conductivity is required to be relatively low, within the conductivity range of semiconductors. Conductive polymers are affected by the preparation process, and their conductivity can fluctuate within a large range. If they are to be put on the market as a stable product, PEDOT products with stable conductivity must be prepared. However, the existing technology uses water as a solvent to prepare PEDOT conductive powder, which has a fast reaction speed, and the reaction process is difficult to control. It is also difficult to accurately and stably prepare relatively low conductivity (the conductivity order of magnitude range is 10 -5 ~10 -3 S / cm). Therefore, it is urgent to propose a method for preparing PEDOT conductive powder with controllable conductivity. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing PEDOT conductive powder with adjustable conductivity, so as to solve the many shortcomings in the preparation of traditional PEDOT powder, such as uncontrollable conductivity, single distribution, complex preparation process, and severe environmental pollution.
[0006] To achieve the above-mentioned purpose, the present invention provides a method for preparing PEDOT conductive powder with controllable conductivity, which uses 3,4-ethylenedioxythiophene monomer as raw material, anhydrous ethanol as solvent, ferric chloride as oxidant, and no other additives are added. By adjusting one or more of the reaction temperature, reaction time and the amount of the oxidant, the preparation of PEDOT conductive powder with different conductivity is achieved.
[0007] Preferably, the preparation method comprises the following steps:
[0008] (1) mixing anhydrous ethanol and EDOT monomer and stirring to dissolve the EDOT monomer to obtain an EDOT solution; dissolving an oxidant ferric chloride in anhydrous ethanol to obtain an anhydrous ethanol solution of the oxidant ferric chloride;
[0009] (2) mixing the EDOT solution with the anhydrous ethanol solution of the oxidant ferric chloride to obtain a mixed reaction system, wherein the molar ratio of EDOT to ferric chloride is 1:(1-10);
[0010] (3) A polymerization reaction occurs at a set reaction temperature to obtain a reaction product, and then the reaction product is separated into a solid and a liquid, washed, and dried to obtain a PEDOT conductive powder.
[0011] Preferably, in step (2), the EDOT solution is mixed with the oxidant ferric chloride in anhydrous ethanol solution, and the ferric chloride in anhydrous ethanol solution is added all at once or added dropwise to the EDOT solution.
[0012] Preferably, the mass percentage of EDOT in the mixed reaction system in step (2) is 1-5%.
[0013] Preferably, the molar ratio of EDOT to ferric chloride in the mixed reaction system of step (2) is 1:(2-5).
[0014] Preferably, the reaction temperature is between 0°C and ethanol reflux temperature, and the reaction time is greater than or equal to 24 hours.
[0015] Preferably, the PEDOT conductive powders with different conductivity have a conductivity between 10 -3 ~10 -5 S / cm order of magnitude range.
[0016] The present invention utilizes ethanol solvent to replace water in the traditional preparation process, transforms the suspension polymerization process into a solution polymerization process, and obtains PEDOT conductive powders with various conductivity by controlling the process conditions without adding any additives. This method has controllable characteristics, and PEDOT powders with different conductivity are obtained by controlling process parameters such as reaction temperature, reaction time or oxidant dosage. At the same time, the product of this preparation process has good stability and high repeatability. Compared with the mainstream PEDOT products currently on the market, this PEDOT powder product has higher processability and a wider range of applications. In general, compared with the prior art, the above technical scheme conceived by the present invention mainly has the following technical advantages:
[0017] (1) The present invention uses ethanol as the solvent for EDOT monomer, which can dissolve EDOT monomer and ferric chloride in the same phase for reaction, and transforms the suspension polymerization process commonly used in the preparation of PEDOT powder into solution polymerization to prepare a PEDOT with a conductivity of 10 -5 ~10 -3 The experiment shows that in an ethanol solvent environment, the higher the amount of oxidant, the higher the temperature, the longer the reaction time, the higher the conversion rate, the lower the conductivity, and the conductivity of the prepared PEDOT powder is stable and controllable.
[0018] (2) Compared with water solvent, ferric chloride is difficult to ionize in ethanol, and the iron ion concentration in the system is reduced, which leads to a decrease in the efficiency of oxidative EDOT polymerization and a decrease in the reaction rate. The present invention has found in experiments that using ethanol as a solvent can inhibit the polymerization of PEDOT to a certain extent, making the degree of polymerization of this polymerization reaction controllable, thereby controlling its conductivity. Therefore, the present invention can control the conductivity of the prepared PEDOT powder by controlling the reaction time, reaction temperature or the amount of oxidant.
[0019] (3) The present invention uses ethanol as the reaction solvent, and the prepared PEDOT conductive powder product has stable performance, simple process flow, easy operation, fewer types of raw materials, less toxic and harmful substances in the raw materials, and low environmental harm, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Reaction route for PEDOT polymerization;
[0021] Figure 2 The process flow chart of the preparation method of the embodiment of the present invention;
[0022] Figure 3 This is the PEDOT powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0024] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0025] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0026] In the present invention, unless otherwise specified and / or described, all numerical values involving the amounts of components are "parts by weight" from beginning to end. The process parameters in the following examples without specifying specific conditions are usually based on conventional conditions.
[0027] The prior art uses chemical oxidation polymerization to prepare PEDOT powder, and generally chooses to react in water solvent. However, due to the fact that EDOT is almost insoluble in water, the water-based suspension precipitation polymerization using water as a solvent to prepare PEDOT conductive particles has a fast reaction speed, is difficult to control the reaction process, is sensitive to environmental influences, and the conductivity of the prepared PEDOT product fluctuates greatly. It is also difficult to prepare a product with stable and low conductivity range (the conductivity order of magnitude range is 10 -5 ~10 - 3 S / cm) of PEDOT powder.
[0028] Based on this, the present invention attempts to use ethanol instead of water as a reaction solvent. Ethanol, as an organic solvent, can dissolve EDOT very well, and the solubility of ferric chloride in ethanol is not low. In addition, the present invention has experimentally found that using ethanol as a solvent can transform the EDOT droplets (oil phase)-iron salt aqueous solution (aqueous phase) when water is used as a solvent into the same phase, and transform the suspension precipitation polymerization into solution precipitation polymerization. After the synthesized PEDOT reaches a certain molecular weight, it is precipitated and dispersed from ethanol. The PEDOT particles prepared in this way are smaller, have better dispersibility, and have simple raw materials and fewer impurities.
[0029] At the same time, since ferric chloride is difficult to ionize in ethanol, ethanol can be used as an EDOT polymerization inhibitor, which can greatly slow down the reaction rate of PEDOT, leaving a large operating space for adjusting the polymerization process parameters. Experiments have found that by controlling the amount of oxidant, polymerization temperature, polymerization reaction time and other process conditions, PEDOT powder with a certain conductivity level can be produced in a controllable, stable and efficient manner. The reaction equation of PEDOT polymerization and the flow chart of the preparation of PEDOT in the present invention are as follows: Figure 1 and Figure 2 shown.
[0030] Specifically, the present invention provides a method for preparing a PEDOT conductive powder with controllable conductivity, which uses 3,4-ethylenedioxythiophene monomer (abbreviated as EDOT) as a raw material, anhydrous ethanol as a solvent, ferric chloride as an oxidant, and no other additives are added. By adjusting one or more of the reaction temperature, reaction time and the amount of the oxidant, the preparation of PEDOT conductive powders with different conductivities is achieved.
[0031] In some embodiments, the preparation method comprises the following steps:
[0032] (1) mixing anhydrous ethanol and EDOT monomer and stirring to dissolve the EDOT monomer to obtain an EDOT solution; dissolving an oxidant ferric chloride in anhydrous ethanol to obtain an anhydrous ethanol solution of the oxidant ferric chloride;
[0033] (2) mixing the EDOT solution with the anhydrous ethanol solution of the oxidant ferric chloride to obtain a mixed reaction system, wherein the molar ratio of EDOT to ferric chloride is 1:(1-10);
[0034] (3) A polymerization reaction occurs at a set reaction temperature to obtain a reaction product, and then the reaction product is separated into a solid and a liquid, washed, and dried to obtain a PEDOT conductive powder.
[0035] In some embodiments, in step (2), an oxidant solution of ferric chloride in anhydrous ethanol is introduced into the EDOT solution, and the ferric chloride in anhydrous ethanol solution is added all at once or added dropwise to the EDOT solution.
[0036] In a preferred embodiment, the anhydrous ethanol solution of ferric chloride is slowly added dropwise to the EDOT solution. The adding time is generally controlled within 2 hours. The solution is added dropwise as evenly as possible to improve the reaction uniformity.
[0037] In some embodiments, the mass percentage of EDOT in the mixed reaction system of step (2) is 1-5%. The molar ratio of EDOT to ferric chloride in the mixed reaction system of step (2) is 1:(2-5).
[0038] In some embodiments, the reaction temperature is between 0°C and ethanol reflux temperature, and the reaction time is greater than or equal to 24 hours.
[0039] In some embodiments, in step (3), the solid product obtained by solid-liquid separation is washed with one or more washing solvents selected from water, anhydrous ethanol, and acetone, preferably water, anhydrous ethanol, and acetone are used for multiple alternating washings. During washing, the solid product obtained by solid-liquid separation is dispersed in water, magnetically stirred and heated to 80-100° C. for continuous dispersion for not less than 30 minutes, and then solid-liquid separation is performed. In some embodiments, the solid product obtained by solid-liquid separation is washed with anhydrous ethanol before drying to improve the drying efficiency.
[0040] The present invention achieves the preparation of PEDOT conductive powders with different electrical conductivities by regulating one or more of the reaction temperature, reaction time and the amount of the oxidant. The conductivity of the PEDOT conductive powders with different electrical conductivities is between 10 -3 ~10 -5 S / cm order of magnitude range.
[0041] In some embodiments, the water described in the present invention is one or more of ultrapure water, deionized water, double distilled water, pure water, and distilled water.
[0042] The present invention provides a method for preparing PEDOT powder with controllable conductivity, high production efficiency and simple process. Both EDOT and ferric chloride can be dissolved in ethanol. Therefore, by using ethanol as a solvent, the polymerization mode can be changed from suspension polymerization to solution polymerization. Ethanol, as an EDOT polymerization inhibitor, can slow down the polymerization rate of EDOT, which is beneficial to control the polymerization reaction of EDOT. The reaction rate and reaction degree of PEDOT are controlled by controlling the amount of oxidant, reaction temperature and reaction time, so as to obtain PEDOT powders with different conductivity.
[0043] The following are specific embodiments:
[0044] Example 1
[0045] S1. Dissolution of EDOT: 50 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer in a room temperature water bath and stirred for 30 min to obtain a completely dissolved EDOT-ethanol solution.
[0046] S2, dropwise addition of ferric chloride: Take 17.11g of anhydrous ferric chloride (3 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the prepared anhydrous ferric chloride ethanol solution to a constant pressure funnel, and slowly drop the anhydrous ferric chloride ethanol solution into the EDOT-ethanol solution at room temperature (25°C), and the dropwise addition time is not less than 2 hours. After the dropwise addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0047] S3. Polymerization of EDOT: Slowly increase the temperature gradually until the temperature reaches the reflux temperature of ethanol. Start timing when the temperature is reached and react for 24 hours.
[0048] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction liquid to obtain a blue-black PEDOT solid. Add 150mL of distilled water to the funnel, stir and disperse the solid, then filter, and repeat 3 times; add 150mL of anhydrous ethanol to the funnel, stir and disperse the solid, then filter, and repeat 3 times. Take out the solid, place it in a 500mL beaker, add 200mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry for 48 hours. The PEDOT solid product after drying is as follows Figure 3 The obtained PEDOT solid product was put into an agate mill and crushed into fine powder, and PEDOT powder was obtained, as shown in FIG. Figure 3 shown.
[0049] Prepared PEDOT powder test:
[0050] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 4.014×10 -3 S / cm.
[0051] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows
[0052]
[0053] Where: m PEDOTis the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected, and the conversion rate of PEDOT was calculated according to this formula to be 92%, with a high yield.
[0054] Example 2
[0055] S1. Dissolution of EDOT: Take 50 mL of anhydrous ethanol and 5 g of EDOT and add them to a conical flask, and add a magnetic stir bar to the conical flask. Then place the conical flask in a magnetic stirrer under a room temperature water bath and stir for 30 minutes to obtain a completely dissolved EDOT-ethanol solution.
[0056] S2, dropwise addition of ferric chloride: Take 13.28g of anhydrous ferric chloride (2.33 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the configured anhydrous ferric chloride solution to a constant pressure funnel, and slowly add the anhydrous ferric chloride ethanol solution to the EDOT-ethanol solution at room temperature (25°C), and the addition time is not less than 2 hours. After the addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0057] S3. Polymerization of EDOT: Slowly increase the temperature gradually until the temperature reaches the reflux temperature of ethanol. Start timing when the temperature is reached and react for 24 hours.
[0058] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction solution is filtered using a G6 sand core funnel to obtain a blue-black PEDOT solid. Add 150 mL of distilled water to the funnel, stir and disperse the solid, and then filter it, repeating 3 times; add 150 mL of anhydrous ethanol to the funnel, stir and disperse the solid, and then filter it, repeating 3 times. Take out the solid, place it in a 500 mL beaker, add 200 mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry it for 48 hours. The obtained PEDOT solid product is put into an agate mill and crushed into fine powder to obtain PEDOT powder.
[0059] Prepared PEDOT powder test:
[0060] 1. The test method of PEDOT conductivity is the same as that in Example 1. The test results show that the conductivity of the PEDOT powder is 9.192×10 - 3 S / cm.
[0061] 2. The PEDOT conversion rate test method is the same as in Example 1, and the calculated PEDOT conversion rate is 87.6%.
[0062] Example 3
[0063] S1. Dissolution of EDOT: Take 50 mL of anhydrous ethanol and 5 g of EDOT and add them to a conical flask, and add a magnetic stir bar to the conical flask. Then place the conical flask in a magnetic stirrer under a room temperature water bath and stir for 30 minutes to obtain a completely dissolved EDOT-ethanol solution.
[0064] S2, the addition of ferric chloride: take 28.52g of ferric chloride hexahydrate (3 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the configured ferric chloride hexahydrate ethanol solution to a constant pressure funnel, and slowly add the ferric chloride hexahydrate ethanol solution to the EDOT-ethanol solution at room temperature (25°C), and the addition time is not less than 2 hours. After the addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0065] S3. Polymerization of EDOT: Slowly increase the temperature gradually until the temperature reaches the reflux temperature of ethanol. Start timing when the temperature is reached and react for 24 hours.
[0066] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction solution is filtered using a G6 sand core funnel to obtain a blue-black PEDOT solid. Add 150 mL of distilled water to the funnel, stir and disperse the solid, and then filter it, repeating 3 times; add 150 mL of anhydrous ethanol to the funnel, stir and disperse the solid, and then filter it, repeating 3 times. Take out the solid, place it in a 500 mL beaker, add 200 mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry it for 48 hours. The obtained PEDOT solid product is put into an agate mill and crushed into fine powder to obtain PEDOT powder.
[0067] Prepared PEDOT powder test:
[0068] 1. The test method of PEDOT conductivity is the same as that in Example 1. The test results show that the conductivity of the PEDOT powder is 2.255×10 - 3 S / cm.
[0069] 2. The PEDOT conversion rate test method was the same as in Example 1, and the calculated PEDOT conversion rate was 89.2%.
[0070] Comparing Example 1 and Example 2, as the amount of oxidant used decreased from 3 times the molar number of EDOT to 2.33 times, the conductivity of the product increased slightly and remained at 10 -3 Comparing Example 1 with Example 3, replacing anhydrous ferric chloride with hexahydrate ferric chloride has no significant effect on the performance of the product.
[0071] Example 4
[0072] S1. Dissolution of EDOT: Take 50 mL of anhydrous ethanol and 5 g of EDOT and add them to a conical flask, and add a magnetic stir bar to the conical flask. Then place the conical flask in a magnetic stirrer under a room temperature water bath and stir for 30 minutes to obtain a completely dissolved EDOT-ethanol solution.
[0073] S2, dropwise addition of ferric chloride: Take 17.11g of anhydrous ferric chloride (3 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the prepared anhydrous ferric chloride ethanol solution to a constant pressure funnel, and slowly drop the anhydrous ferric chloride ethanol solution into the EDOT-ethanol solution at room temperature (25°C), and the dropwise addition time is not less than 2 hours. After the dropwise addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0074] S3. Polymerization of EDOT: slowly increase the temperature to 50°C, start timing when the temperature is reached, and react for 12 hours; slowly increase the temperature to the ethanol reflux temperature, and react for 12 hours when the temperature is reached.
[0075] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction solution is filtered using a G6 sand core funnel to obtain a blue-black PEDOT solid. Add 150 mL of distilled water to the funnel, stir and disperse the solid, and then filter it, repeating 3 times; add 150 mL of anhydrous ethanol to the funnel, stir and disperse the solid, and then filter it, repeating 3 times. Take out the solid, place it in a 500 mL beaker, add 200 mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry it for 48 hours. The obtained PEDOT solid product is put into an agate mill and crushed into fine powder to obtain PEDOT powder.
[0076] Prepared PEDOT powder test:
[0077] 1. The test method of PEDOT conductivity is the same as that in Example 1. The test results show that the conductivity of the PEDOT powder is 6.346×10 - 4 S / cm.
[0078] 2. The PEDOT conversion rate test method is the same as in Example 1, and the calculated PEDOT conversion rate is 80%.
[0079] Example 5
[0080] S1. Dissolution of EDOT: 50 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer in a room temperature water bath and stirred for 30 min to obtain a completely dissolved EDOT-ethanol solution.
[0081] S2, dropwise addition of ferric chloride: Take 22.82g of anhydrous ferric chloride (4 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the configured anhydrous ferric chloride ethanol solution to a constant pressure dropping funnel, and slowly add the anhydrous ferric chloride ethanol solution to the EDOT-ethanol solution at room temperature (25°C), and the addition time is not less than 2 hours. After the addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0082] S3. Polymerization of EDOT: slowly increase the temperature to 50°C, start timing when the temperature is reached, and react for 12 hours; slowly increase the temperature to the ethanol reflux temperature, and react for 12 hours when the temperature is reached.
[0083] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction solution is filtered using a G6 sand core funnel to obtain a blue-black PEDOT solid. Add 150 mL of distilled water to the funnel, stir and disperse the solid, and then filter it, repeating 3 times; add 150 mL of anhydrous ethanol to the funnel, stir and disperse the solid, and then filter it, repeating 3 times. Take out the solid, place it in a 500 mL beaker, add 200 mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry it for 48 hours. The obtained PEDOT solid product is put into an agate mill and crushed into fine powder to obtain PEDOT powder.
[0084] Prepared PEDOT powder test:
[0085] 1. The test method of PEDOT conductivity is the same as that in Example 1. The test results show that the conductivity of the PEDOT powder is 1.240×10 - 4 S / cm.
[0086] 2. The PEDOT conversion rate test method was the same as in Example 1, and the calculated PEDOT conversion rate was 91.4%.
[0087] Comparing Example 1 with Example 4, the time of ethanol reflux temperature reaction was shortened from 24 hours in Example 1 to 12 hours in Example 2, and the conductivity was significantly reduced by one order of magnitude; the conversion rate also decreased significantly, but remained at a high level. Comparing Example 4 with Example 5, as the amount of oxidant used increased from 3 times the molar number of EDOT to 4 times, the conductivity of the product decreased, but the conversion rate of the product increased significantly.
[0088] Example 6
[0089] S1. Dissolution of EDOT: 50 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer in a room temperature water bath and stirred for 30 min to obtain a completely dissolved EDOT-ethanol solution.
[0090] S2, dropwise addition of ferric chloride: Take 17.11g of anhydrous ferric chloride (3 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the prepared anhydrous ferric chloride ethanol solution to a constant pressure funnel, and slowly drop the anhydrous ferric chloride ethanol solution into the EDOT-ethanol solution at room temperature (25°C), and the dropwise addition time is not less than 2 hours. After the dropwise addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0091] S3. Polymerization of EDOT: Slowly increase the temperature to 50°C, start timing after reaching the temperature, and react for 60 hours.
[0092] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction solution is filtered using a G6 sand core funnel to obtain a blue-black PEDOT solid. Add 150 mL of distilled water to the funnel, stir and disperse the solid, and then filter it, repeating 3 times; add 150 mL of anhydrous ethanol to the funnel, stir and disperse the solid, and then filter it, repeating 3 times. Take out the solid, place it in a 500 mL beaker, add 200 mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry it for 48 hours. The obtained PEDOT solid product is put into an agate mill and crushed into fine powder to obtain PEDOT powder.
[0093] Prepared PEDOT powder test:
[0094] 1. The test method of PEDOT conductivity is the same as that in Example 1. The test results show that the conductivity of the PEDOT powder is 1.202×10 - 5 S / cm.
[0095] 2. The PEDOT conversion rate test method was the same as in Example 1, and the calculated PEDOT conversion rate was 86.2%.
[0096] Example 7
[0097] S1. Dissolution of EDOT: 50 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer in a room temperature water bath and stirred for 30 min to obtain a completely dissolved EDOT-ethanol solution.
[0098] S2, dropwise addition of ferric chloride: Take 14.26g of anhydrous ferric chloride (2.5 times the molar number of EDOT) and dissolve it in 90mL of anhydrous ethanol, and stir for a long time to completely dissolve the ferric chloride. Move the configured anhydrous ferric chloride ethanol solution to a constant pressure dropping funnel, and slowly add the anhydrous ferric chloride ethanol solution to the EDOT-ethanol solution at room temperature (25°C), and the addition time is not less than 2 hours. After the addition is completed, wash the glassware with 10mL of anhydrous ethanol, and add the washing liquid to the reaction solution.
[0099] S3. Polymerization of EDOT: Slowly increase the temperature to 50°C, start timing after reaching the temperature, and react for 60 hours.
[0100] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction solution is filtered using a G6 sand core funnel to obtain a blue-black PEDOT solid. Add 150 mL of distilled water to the funnel, stir and disperse the solid, and then filter it, repeating 3 times; add 150 mL of anhydrous ethanol to the funnel, stir and disperse the solid, and then filter it, repeating 3 times. Take out the solid, place it in a 500 mL beaker, add 200 mL of distilled water, add a magnetic stirrer, put it in an 80°C water bath magnetic stirrer and stir for 30 minutes, then take it out and continue to use a G6 sand core funnel to filter. After repeating this step 6 times, use anhydrous ethanol to stir, disperse and filter, then put the sand core funnel containing the solid product into a vacuum drying oven, set the temperature to 80°C, and dry it for 48 hours. The obtained PEDOT solid product is put into an agate mill and crushed into fine powder to obtain PEDOT powder.
[0101] Prepared PEDOT powder test:
[0102] 1. The test method of PEDOT conductivity is the same as that in Example 1. The test results show that the conductivity of the PEDOT powder is 1.846×10 - 5 S / cm.
[0103] 2. The PEDOT conversion rate test method is the same as in Example 1, and the calculated PEDOT conversion rate is 74%.
[0104] Comparing Example 6 and Example 7, as the amount of oxidant used decreased from 3 times the molar number of EDOT to 2.5 times, the conductivity of the product increased slightly and remained at 10 -5 The conversion rate of the product decreased significantly, which is consistent with the comparison between Example 1 and Example 2.
[0105] By comparing Example 1, Example 4, and Example 6, it can be concluded that in an anhydrous ethanol reaction system in which the amount of oxidant used is 3 times the molar number of EDOT, when the reaction temperature and time are limited to ethanol reflux temperature-24h, 50°C-12h-ethanol reflux temperature-12h, and 50°C-60h, respectively, the conductivity between 10 -3 S / cm, 10 -4 S / cm, 10 -5 The PEDOT semiconductor powder product has a S / cm order of magnitude and can ensure a conversion rate of no less than 80%.
[0106]
[0107]
[0108] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing PEDOT conductive powder with controllable conductivity, characterized in that: Using 3,4-ethylenedioxythiophene monomer as raw material, anhydrous ethanol as solvent, ferric chloride as oxidant, and adjusting one or more of reaction temperature, reaction time and amount of oxidant, the preparation of PEDOT conductive powders with different electrical conductivities is achieved.
2. The preparation method according to claim 1, characterized in that The steps include: (1) mixing anhydrous ethanol and EDOT monomer and stirring to dissolve the EDOT monomer to obtain an EDOT solution; dissolving an oxidant ferric chloride in anhydrous ethanol to obtain an anhydrous ethanol solution of the oxidant ferric chloride; (2) mixing the EDOT solution with the anhydrous ethanol solution of the oxidant ferric chloride to obtain a mixed reaction system, wherein the molar ratio of EDOT to ferric chloride is 1:(1-10); (3) A polymerization reaction occurs at a set reaction temperature to obtain a reaction product, and then the reaction product is separated into a solid and a liquid, washed, and dried to obtain a PEDOT conductive powder.
3. The preparation method according to claim 2, characterized in that: Step (2) mixing the EDOT solution with the oxidant ferric chloride in anhydrous ethanol solution, wherein the ferric chloride in anhydrous ethanol solution is added all at once or added dropwise to the EDOT solution.
4. The preparation method according to claim 2, characterized in that: The mass percentage of EDOT in the mixed reaction system in step (2) is 1-5%.
5. The preparation method according to claim 2, characterized in that: The molar ratio of EDOT to ferric chloride in the mixed reaction system of step (2) is 1:(2-5).
6. The preparation method according to claim 2, characterized in that: The reaction temperature is between 0°C and ethanol reflux temperature, and the reaction time is greater than or equal to 24 hours.
7. The preparation method according to claim 2, characterized in that: In step (3), the solid product obtained by solid-liquid separation is washed with one or more washing solvents selected from water, anhydrous ethanol and acetone, preferably water, anhydrous ethanol and acetone are used for multiple alternating washings.
8. The preparation method according to claim 2, characterized in that: During washing, the solid product obtained by the solid-liquid separation is dispersed in water, magnetically stirred and heated to 80-100° C. for continuous dispersion for no less than 30 minutes, and then solid-liquid separation is performed.
9. The preparation method according to claim 1, characterized in that: The conductivity of the PEDOT conductive powders with different conductivity is between 10 -3 ~10 -5 S / cm order of magnitude range.
Citation Information
Patent Citations
Preparation method of oxidant as well as doping agent for synthesizing conductive high polymer
CN102557993A
Method of imparting antistatic properties to a substrate by coating the substrate with a novel polythiophene
US5035926A